Variations in The Number of Roots and Root Canals in Maxillary Second Molars- A Review of Literature - DHAYANITHI, J.; K, DR. ANJANEYULU.; BRUNDHA, DR.M.P. (The journal of contemporary issues in business and government, 2021)
The dental professional should be familiar with the differences of number of root and root canal system anatomy, which at some aspects provides specific dental anomalies of tooth and helpful in analysing in the clinical field. The main aim for patients and doctors is to relive pain and maintain natural teeth with similar morphology. Root canal therapy is mostly the treatment of choice for teeth with pulpal and periradicular affected teeth. Effective treatment is required for good mechanical and chemical cleaning and shaping and provides a compact obturation under aseptic conditions with an inert filling material.The major reason for endodontic failure is the existence of untreated canals. A detailed diagnosis of the root canal system anatomy is a requirement for effective treatment of root canals. This review shows incidence of root and root canal variations in maxillary second molars. The presence of root canal orifices helps in diagnosis of preoperative radiographs and examination of the pulp.